Evaluation of digital libraries: Criteria and problems from users' perspectives - (Iris) Xie, Hong (Library & information science research, 2006)
Digital library research has developed over the past decade, but little has been done on the identification of evaluation criteria, especially from users' perspectives. This article identifies users' criteria and applies them to the evaluation of existing digital libraries. Forty-eight subjects were instructed to develop and justify a set of essential criteria for the evaluation of digital libraries. At the same time, they were requested to evaluate existing digital libraries by applying the criteria that they were developing. A compilation of criteria developed by participants show that usability and collection quality were the most important criteria for evaluating digital libraries. Service quality, system performance efficiency, and user opinion solicitation were also deemed essential criteria. The author further compares digital library evaluation criteria identified by users and researchers and applied in previous research. The article reveals problems in current digital library design and development, discusses suggestions for improving digital library design, and presents areas for further research.